Revision of Isoplenodia Prout, 1932 with new records from continental Africa (Lepidoptera: Geometridae, Sterrhinae) - Sihvonen, Pasi; Staude, Hermann S. (Zootaxa, 2010)
Three new species of Isoplenodia Prout, 1932 are described and illustrated from continental Africa, expanding the taxonomic scope and known geographic distribution of this previously endemic, monotypic Madagascan genus of geometrid moths. The new species are: I. vidalensis Sihvonen & Staude sp. n., from eastern South Africa; I. kisubiensis Sihvonen & Staude sp. n., from southern Uganda; and I. arabukoensis Sihvonen & Staude sp. n., from southeastern Kenya, central Zimbabwe and southwestern Rwanda. The paucity of available data suggest that the African species may be associated with wet forest or marsh mosaic habitats. Adults and genitalia of all known Isoplenodia species are illustrated, and the systematic position of the genus in relation to other genera in the tribe Scopulini is discussed.